A Phonological Appraisal of the Central Kurdish Writing Systems - Rasty A. Hama Saeed; Twana S. Hamid (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
The Kurds used Arabic, Persian and Turkish writing systems until the beginning of the last century. Since then, a modified system of Arabic script was proposed to Kurdish and came to use. Parallel to the modified Arabic script, some linguists have called to a Latin-based writing system. Based on phonological evidence, this study looks into the suitability of the writing systems to the Central Kurdish variety. It assesses the phoneme-grapheme relation in both ways: letters corresponding to phonemes and phonemes corresponding to letters. Since the Central Kurdish writing system is phonemic, the study tries to find out which writing system regularly and consistently represents the phonemes. The study reaches the conclusion that both systems have advantages and disadvantages. The Perso-Arabic Script better represents the phonemic inventory of Central Kurdish. In particular, it can provide codes for the pharyngeal phonemes entered the language through language contact from the neighbouring languages. Moreover, teaching the Perso-Arabic Script to current and upcoming generations will familiarise them with the writing system used for classic literature. However, the Latin-based system better suits modern day software programs and keyboards.